2007
DOI: 10.1002/chem.200700467
|View full text |Cite
|
Sign up to set email alerts
|

Is This a Chemical Bond? A Theoretical Study of Ng2@C60(Ng=He, Ne, Ar, Kr, Xe)

Abstract: Quantum-chemical calculations using DFT (BP86) and ab initio methods (MP2, SCS-MP2) have been carried out for the endohedral fullerenes Ng2@C60 (Ng=He-Xe). The nature of the interactions has been analyzed with charge- and energy-partitioning methods and with the topological analysis of the electron density (Atoms-in-Molecules (AIM)). The calculations predict that the equilibrium geometries of Ng2@C60 have D3d symmetry when Ng=Ne, Ar, Kr, while the energy-minimum structure of Xe2@C60 has D5d symmetry. The prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 63 publications
10
197
1
Order By: Relevance
“…Comprehensively, the He atom and the N atom interact with each other only through a van der Waals interaction inside the C 60 cage, whose situation is similar to that of He 2 @C 60 (ref. 37). The present result clearly showed that a single atom of helium in C 60 is observable by means of single crystal X-ray analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensively, the He atom and the N atom interact with each other only through a van der Waals interaction inside the C 60 cage, whose situation is similar to that of He 2 @C 60 (ref. 37). The present result clearly showed that a single atom of helium in C 60 is observable by means of single crystal X-ray analyses.…”
Section: Discussionmentioning
confidence: 99%
“…2. In this complex, two He atoms are located at a distance of 1.979Å (unlike 1.948Å, as in work [90]) from each other. Each He atom is located at a distance of about 2.507Å (2.671Å in work [90]) from the C-C bond in the C 60 pentagon.…”
Section: Calculation Techniquementioning
confidence: 98%
“…In this complex, two He atoms are located at a distance of 1.979Å (unlike 1.948Å, as in work [90]) from each other. Each He atom is located at a distance of about 2.507Å (2.671Å in work [90]) from the C-C bond in the C 60 pentagon. The Mulliken charge of an He atom equals = +0.011 e. The calculated frequency (He-He) = 69.6 cm −1 describes the motion of the diatomic dumbbell-like complex He-He, which was also mentioned earlier in work [90, p. 8260] 9 .…”
Section: Calculation Techniquementioning
confidence: 98%
See 2 more Smart Citations